Level of Knowledge about Tuberculosis among Type 2 Diabetes Mellitus Patients at the Endocrine Clinic Dr. Hasan Sadikin General Hospital Bandung - Ulfah Dwi Febriani; Rovina Ruslami; Bachti Alisjahbana (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Diabetes Mellitus (DM) is one of the risk factors for tuberculosis (TB). Knowledge of TB is essential in prevention control for the person at risk. This study aimed to describe the level of knowledge about TB among DM patients.Methods: A cross sectional study was performed involving 72 adult DM patients at the Endocrine Clinic, Dr. Hasan Sadikin General Hospital Bandung. The subjects were interviewed using a standardized questionnaire including socio-demographic information and knowledge about TB: manifestation of TB, transmission, treatment, DM-TB co-infections, and status acquiring TB information in the last 12 months. Knowledge was categorized as high, moderate and low if total scores were >75, 56–75 and <56 respectively. Data were presented descriptively as percentage and mean (SD) after testing for the normality of distribution.Results: The mean of age of subjects was 56.6 years, and 55% were female. Most were unemployed (72.2%), had an education background lower than high school (75%), and lived in Bandung (91.7%). The mean score of knowledge was 54.4. Proportion of subjects based on the level of knowledge which is high, moderate and low, were 29.2%, 26.4%, and 44.4% respectively. Conclusions: The level of knowledge about TB among Type 2 DM patients at the Endocrine Clinic Dr. Hasan Sadikin General Hospital Bandung was low. TB education program among DM patients needs to be improved.